THE EFFECT OF HEALTH EDUCATION BY THE ROLE PLAY METHOD ON KNOWLEDGE LEVEL ABOUT PREVENTION OF SEXUAL VIOLENCE IN SCHOOL AGES - Meilinda Ulfah Adha Suhenda; Tetti Solehati; Ai Mardhiyah (Ikatan Perawat Maternitas Indonesia Provinsi Jawa Barat, 2019)
Cases of child sexual violence (KSA) in Bandung Regency continue to increase, and cause physical, psychological, growth, development and traits in the future. KSA prevention education is needed as primary prevention to increase children's knowledge in order to protect themselves. This study aimed to analyze the effect of education through the role play method on the level of knowledge regarding the prevention of school-age KSA in Solokan Garut Elementary School, Bandung Regency. This type of research was Pre-Experimental with One group pre and post-test design. Sample selection used purposive sampling techniques. The study involved 47 respondents from grade 1 and 2 students at Solokan Garut Elementary School in Bandung Regency. The treatment in the form of education to prevent KSA at school age uses the